2000
DOI: 10.1524/zkri.2000.215.9.542
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational structural study of two hindered aminoanthraquinones in crystals and solutions

Abstract: The crystal and molecular structures of 2-methyl-1-methylamino-anthraquinone (I) and 1-methylphenylamino-anthraquinone (II) were studied by the X-ray singlecrystal diffraction and the visible spectra of crystalline specimens and their solutions were recorded. The molecule I is closely planar, whereas in the molecule II the amino group is 58 rotated out of the plane of the anthraquinone skeleton. In both structures the molecules pack in stacks. The comparison of experimental and calculated (on the DFT and AM1 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In the molecule of the title compound, likewise in the 1-dimethylamino-9,10-anthraquinone [46] and 1-[methyl(phenyl)amino]anthraquinone [47], a deviation from planarity of the anthraquinone skeleton is observed. However, the rings, composed of atoms C 1 , C 2 , C 3 , C 4 , C 5 , C 6 and C 8 , C 9 , C 12 , C 13 , C 15 , C 16 , do not show any significant deviation from planarity.…”
Section: Geometrical Parametersmentioning
confidence: 90%
“…In the molecule of the title compound, likewise in the 1-dimethylamino-9,10-anthraquinone [46] and 1-[methyl(phenyl)amino]anthraquinone [47], a deviation from planarity of the anthraquinone skeleton is observed. However, the rings, composed of atoms C 1 , C 2 , C 3 , C 4 , C 5 , C 6 and C 8 , C 9 , C 12 , C 13 , C 15 , C 16 , do not show any significant deviation from planarity.…”
Section: Geometrical Parametersmentioning
confidence: 90%
“…In the molecule of the title compound ( Fig. 1), likewise in the 1-dimethylamino-9,10-anthraquinone (Niedziałkowski et al, 2011) and 1-[methyl(phenyl)amino]anthraquinone (Yatsenko et al, 2000), deviation of planarity of the anthraquinone skeleton is observed. In case of the title compound, such distortion is found to be 0.0885 (3…”
Section: D-hámentioning
confidence: 89%
“…For general background to and applications of anthraquinone derivatives, see: Alves et al (2004); Czupryniak et al (2012); Wang et al (2011); Yeh & Wang (2006). For related structures, see: Niedziałkowski et al (2011); Yatsenko et al (2000).…”
Section: Related Literaturementioning
confidence: 99%
“…In the molecule of the title compound ( Fig. 1), likewise in the 1-(methyl(phenyl)amino)anthraquinone (Yatsenko et al, 2000), relatively strong deviation of planarity of the anthraquinone skeleton is observed. In case of the title compound, such distortion (0.1274 (3) Å) is directly caused by the steric effect of the bulky -N(CH 3 ) 2 group (Dalliya et al, 2007).…”
Section: Data Collectionmentioning
confidence: 91%
“…For general background to anthraquinones, see: Arai et al (1985); Dalliya et al (2007); Gatto et al (1996); Kowalczyk et al (2010); Mori et al (1990); Ossowski et al (2005); Zoń et al (2003). For a related structure, see: Yatsenko et al (2000). For molecular interactions, see: Hunter et al (2001); Spek (2009); Takahashi et al (2001).…”
Section: Related Literaturementioning
confidence: 99%